2018
DOI: 10.1111/1365-2664.13279
|View full text |Cite
|
Sign up to set email alerts
|

Developing the global potential of citizen science: Assessing opportunities that benefit people, society and the environment in East Africa

Abstract: 1. Citizen science is gaining increasing prominence as a tool for science and engagement. However, despite being a potentially valuable tool for sustainable development, citizen science has little visibility in many developing countries.2. We undertook a collaborative prioritisation process with experts in conservation and the environment to assess the potential of environmental citizen science in East Africa, including its opportunities, benefits and barriers. This provided principles that are applicable acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
75
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 117 publications
(106 citation statements)
references
References 20 publications
5
75
0
1
Order By: Relevance
“…; Pocock et al . ). We have demonstrated that the establishment of the NBC, which included provincial coordinators, was a key contributor to data collection about honey bee colony losses in Argentina.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…; Pocock et al . ). We have demonstrated that the establishment of the NBC, which included provincial coordinators, was a key contributor to data collection about honey bee colony losses in Argentina.…”
Section: Discussionmentioning
confidence: 97%
“…Although there is a general desire to foster citizen science in developing countries (Pocock et al . ) with a view to establishing international and global projects (Chandler et al . ), the techniques used to collect data through citizen‐science initiatives in developed countries may not work in developing countries (Danielsen et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations